Letter to Harry Ashmore from Charles Warren - Charles Warren:::::: (1967)
A letter from Charles Warren that informs Harry Ashmore that Frank Stead has been appointed Chairman of the Task Force on Human Environment. Warren notes that Stead will receive the names of Advisory Committee members interested in serving and that members will be notified of his appointment. He adds that Stead understands the need to prepare a preliminary report in time for the January conference in Fresno and expresses confidence in the quality of the forthcoming report.